Sistematic Literature Review: The Effect of Tax Planning and Tax Management on Financial Performance - Santoso, Rizki Agung; Harefa, Tulus; Mukhtaruddin, Mukhtaruddin (Dinasti International Journal of Management Science, 2025)
Tax planning and tax management are strategies used by companies to optimize tax obligations to improve financial efficiency and minimize tax risks. This study aims to identify research gaps and understand the relationship between tax planning, tax management, and tax strategies on financial performance. The method used in this research is Sistematic Literature Review (SLR) by analyzing 25 academic literatures from scientific databases such as Garuda, Sinta, ResearchGate, MDPI, and Springer in the 2020-2025 publication period. This study highlights tax regulations, corporate governance, financial transparency, and industry characteristics that influence tax strategies. The results reveal that there are inconsistencies in the results of previous studies, especially regarding the effect of tax planning and earnings management on tax strategies. Some studies find that tax planning can improve financial performance, while other studies show that aggressive tax strategies risk reducing financial transparency and stability. In addition, it was found that external factors such as tax policy, corporate governance, and international regulations have a significant role in shaping corporate tax strategies. This finding confirms that the effectiveness of tax strategies does not only depend on internal corporate factors, but is also influenced by regulatory dynamics and macroeconomic factors. This study has limitations in the scope of the literature analyzed, so future studies are expected to expand references and deepen the analysis of tax strategies in various industrial sectors and different jurisdictions.